A Dual Authenticated Safety Vault for Cryopreservation Center - et. al., Arthi. R, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the most rapidly developing century , one critical issue that has been confronted was in providing security to the houses, offices and vaults. Though the physical surveillance such as CCTV cameras at the areas required has been used , they are only useful for the further investigation of any kinds of burglary and theft. Many security code or combination lock systems are also used are mostly hackable and decodable and hence it always needs to be improved and novel techniques are to be introduced to improve security. This paper therefore proposes a dual authenticated digital code lock system wherein the digital code is of total the 8 digits in which 4 digits of the code are user-defined and the remaining 4 are server generated digits and changes for every individual entry[commonly known as OTP(One Time Password)]. The important and the most reliable part of the proposed digital code lock system is the positions of the user-defined and server generated digits is also user-defined, which makes cracking or hacking the code more complex and also time consuming. The proposed dual authenticated safety vault has its applications in the area of safe guarding cryopreserving centre, medical documents, bank safety locker, residential homes and hotels.